2002
DOI: 10.1086/502012
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Recombinant Hepatitis B Vaccine for Healthcare Workers Who Fail to Respond to Intramuscular Vaccine

Abstract: Objective:To study the humoral immune responses, safety, and tolerability of intradermal recombinant hepatitis B vaccination in healthcare workers (HCWs) nonresponsive to previous repeated intramuscular vaccination.Design:An open, prospective, before–after trial.Setting:A tertiary referral hospital and surrounding district health service in Queensland, Australia.Participants:Hospital and community HCWs nonresponsive to previous intramuscular hepatitis B vaccination.Methods:Intradermal recombinant hepatitis B v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…Additional studies using rPA doses within the 10-g-to 0.2-g range will be required to further elucidate the potential dose-sparing benefits of the i.d. route, as have been observed for other vaccines (1,2,10,12,20,22).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Additional studies using rPA doses within the 10-g-to 0.2-g range will be required to further elucidate the potential dose-sparing benefits of the i.d. route, as have been observed for other vaccines (1,2,10,12,20,22).…”
Section: Discussionsupporting
confidence: 68%
“…However, recent studies demonstrate that vaccine delivery to the skin can increase the magnitude of the immune response and, in some cases, do so using less vaccine than required with i.m. injection (1,2,10,12,(18)(19)(20)22). For example, clinical studies evaluating intradermal (i.d.)…”
mentioning
confidence: 99%
“…Our finding that CD4 T cells generated by the higher DNA vaccination dose were greater in magnitude and function (i.e., the ability to secrete three cytokines and upregulate CD154) demonstrates that the dose is an important factor in determining the quality of immune responses. Despite the improved CD4 T-cell responses induced by the high-dose DNA, the subsequent administration of a recombinant gp120 protein did not boost this response, indicating either the ineffectiveness of the protein along with the QS-21 adjuvant to boost CD4 without subsequent priming or a null or even detrimental effect of repeated vaccinations with (4,9,24,31,36,49,53,64,69,78). These trials have generally used particle-based vaccines, but one trial demonstrated that antibody responses in volunteers receiving a hepatitis B vaccine i.d.…”
Section: Discussionmentioning
confidence: 99%
“…Playford et al (2002) (23) observaram que 94% (17/18) dos trabalhadores da saúde que não responderam à vacinação intramuscular responderam quando imunizados por via intradérmica. Baldy et al (2003) (2) avaliaram a utilização de três doses de 2 µg de vacina Engerix® B em 135 dentistas por via intradérmica.…”
unclassified